Neurochemical Plasticity of the Coeliac-Superior Mesenteric Ganglion Complex Neurons Projecting to the Prepyloric Area of the Porcine Stomach following Hyperacidity - Katarzyna Palus; Jarosław Całka (Neural Plasticity)
This study was designed to determine neurochemical properties of the coeliac-superior mesenteric ganglion (CSMG) neurons supplying the prepyloric area of the porcine stomach in physiological state and following experimentally induced hyperacidity. To localize sympathetic neurons innervating the studied area of stomach, the neuronal retrograde tracer Fast Blue (FB) was applied to control animals and hydrochloric acid infusion (HCl) groups. After 23 days, animals of the HCl group were reintroduced into a state of general anesthesia and intragastrically given 5 mL/kg of body weight of 0.25 M aqueous solution of hydrochloric acid. On the 28th day, all animals were sacrificed. The CSMG complexes were then collected and processed for double-labeling immunofluorescence. In the control animals, FB-positive perikarya displayed immunoreactivity to tyrosine hydroxylase (TH), dopamine β-hydroxylase (DβH), neuropeptide Y (NPY), and galanin (GAL). Experimentally induced gastric hyperacidity changed the neurochemical phenotype of the studied neurons. An upregulated expression of GAL and NPY and the de novo synthesis of neuronal nitric oxide synthase (nNOS) and leu5-enkephalin (LENK) as well as downregulated expression of TH and DβH in the stomach-projecting neurons were observed. These findings enrich existing knowledge about the participation of these active substances in adaptive mechanism(s) of the sympathetic neurons during pathological processes within the gastrointestinal tract.